(untitled) (Fiep Bulletin - online, 2013)
ABSTRACT In professional athletes, sports injuries are common due to high demands of practice. However, they are not exclusive to top athletes. This descriptive study aimed to investigate some inferior limb injuries characteristics in amateur sports that involve jumping (volleyball, basketball and handball). 37 male amateur athletes participated in the study: 14 volleyball players (age 23,8±2,9), 14 basketball players (age 16,1±1,7) and 9 handball players (age 22,2±1,4) with practice time of 7,7±3,6; 3,4±1,0 and 7,1±2,7 years, respectively. A questionnaire was used to investigate the characteristics of the injuries; a video camera and a form were used to record the number of jumps of each athlete during a period of three game-trainings in each sport. The data were analyzed by descriptive statistics (average, standard deviation and variation coefficient) and inferential statistics (ANOVA one way and simple linear regression) with 5 % significance level. The number of injuries was higher in basketball athletes (35), followed by volleyball (24) and handball (10). The average number of jumps for athlete was significantly lower in handball (9,4±2,1), and it had no differences between volleyball (48,3±22) and basketball (56,3±28,5). There was a significant relationship between jumps and injuries numbers, considering all the sports together (R2=0,20; p=0,02). We can conclude that the injuries number suffered by amateur athletes in the inferior limbs was high, and that this occurs probably due to the lack of landing techniques used during jumping.